2015
DOI: 10.1515/acs-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the first step of SPLET mechanism: O–H bond cleavage in the mono-substituted benzoic acids

Abstract: The first step of SPLET mechanism in solution phase for 15 benzoic acid derivatives was studied from the thermodynamic point of view. For this purpose, proton affinities (PAs) of corresponding carboxylate or phenoxide anions were computed by means of DFT method employing B3LYP and M062X functionals with 6-311++G** basis set and SMD or IEF-PCM solvent model. The substituent effect on PAs was analyzed in terms of Hammett constants, σp. Found dependences exhibit satisfactory linearity and enable quick estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In last years, newer M05-2X and M06-2X functional with SMD solvation model are also applied in the thermodynamics of antioxidant action works -including the reactions of gallic acid with various free radicals (Đorović, 2014). These provide identical trends in BDE, IP, PDE, PA and ETE, although a shift in the absolute values obtained using different functional and/or solvation model can be observed (Marković, 2013;Škorňa, 2016;Marković, 2016;Michalík, 2015). For ortho-, meta-, and para-substituted hydroxybenzoic acids, it was found that the shift in calculated proton affinities can be attributed mainly to the employed solvation model (Michalík, 2015) -values obtained using B3LYP and M06-2X functionals with the same solvation models were in very good mutual agreement, while application of SMD model led to PA values lower by ca 80 kJ mol -1 in comparison to those obtained from IEF-PCM calculations.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In last years, newer M05-2X and M06-2X functional with SMD solvation model are also applied in the thermodynamics of antioxidant action works -including the reactions of gallic acid with various free radicals (Đorović, 2014). These provide identical trends in BDE, IP, PDE, PA and ETE, although a shift in the absolute values obtained using different functional and/or solvation model can be observed (Marković, 2013;Škorňa, 2016;Marković, 2016;Michalík, 2015). For ortho-, meta-, and para-substituted hydroxybenzoic acids, it was found that the shift in calculated proton affinities can be attributed mainly to the employed solvation model (Michalík, 2015) -values obtained using B3LYP and M06-2X functionals with the same solvation models were in very good mutual agreement, while application of SMD model led to PA values lower by ca 80 kJ mol -1 in comparison to those obtained from IEF-PCM calculations.…”
Section: Introductionmentioning
confidence: 70%
“…For ortho-, meta-, and para-substituted hydroxybenzoic acids, it was found that the shift in calculated proton affinities can be attributed mainly to the employed solvation model (Michalík, 2015) -values obtained using B3LYP and M06-2X functionals with the same solvation models were in very good mutual agreement, while application of SMD model led to PA values lower by ca 80 kJ mol -1 in comparison to those obtained from IEF-PCM calculations. Analogous, very uniform shift was found also for IEF-PCM and SMD solution-phase proton affinities of 14 para-substituted benzoic acids with various electron-donating and electron-withdrawing substituents (Michalík, 2015).…”
Section: Introductionmentioning
confidence: 85%
“…The reason of the reduced activity of compound 8 might be the presence of free carboxylic group: it is well-known that the first step of SPLET (sequential proton loss and electron transfer) mechanism that dominates in polar media strongly depends on proton affinity of reacting site. Quantum calculation results are not conclusivewhether hydroxyl or carboxyl group is more likely to react the first, is not known [11]. Alugram ® SIL G/UV254 plates were eluated with CHCl3 for N,N`-diarylmalonamides 2 or with CHCl3:EtOAc (1:1, v:v) for arylidenemalonic acid dianilides 1.…”
Section: Resultsmentioning
confidence: 99%